Mechanical Properties and Corrosion Characteristics of Dissimilar Friction Stir Welded AA1000/AA6061-T6 Aluminum Alloys - Chhorn Sokvisal; Mochammad Noer Ilman (Departemen Teknik Mesin dan Industri, Universitas Gadjah Mada, 2023)
This paper is aimed to investigate microstructure, corrosion and mechanical properties of dissimilar metal weld joints between AA1000 and AA6061-T6 under different tool rotational speeds of 910, 1500, and 2280 rpm at a constant transverse speed of 30 mm/min. Several experimental works have been conducted including microstructure observation using optical microscopy and Scanning Electron Microscopy (SEM) equipped with Energy Dispersive X-ray Spectroscopy (EDS), Vickers microhardness measurements, tensile tests, and corrosion measurements using Potentiodynamic Polarization method. Results show that increasing tool rotational speed from 910 rpm to 1500 rpm increases the degree of homogeneity in nugget zone and improves strength of the weld joint but further increase in the tool rotational speed up to 2280 rpm degrades the mechanical properties due to coarsening of the microstructure. Furthermore, corrosion rate of the nugget zone (NZ) is in between the two base metals.